Unexpectedly two storied tin shed collapse: A case study of urban hazard in Dhaka city, Bangladesh - Alam, Mohammad Feruj; Hossain, Munir; Hossain, Md Azahar (Journal of Nepal Geological Society, 2018)
The study has been carried out for an urban hazard analyses to find out the engineering geological characteristics of subsurface sediments and causes of two storied tin shed unexpectedly and suddenly collapsed and submerged in Rampura valley, Dhaka city, Bangladesh on the 15 April, 2015. Total 12 people were spot died due to collapsed tin shed. The area is covered by valley and this valley is composed of organic material, clayey silt, silty sand and sandy silt. Atterberg limit test indicates that the sediments are slightly plastic and low compressibility inorganic silts. Specific gravity of the sediments varies from 2.66 to 2.68, natural moisture content about 34.5%, dry density about 1.37 gm/cc, wet density about 1.84 gm/cc and unconfined compression strength about 45.9 Kpa. From this result, it reveals that shallow foundation is not suitable for the study area but deep foundation particularly pile foundation would be required. Five major possible causes have been identified for this incident, these are (1) presence of a valley and valley deposits, (2) very soft organic clay and soft slightly plastic clayey silt, (3) poor quality construction materials of shed and shallow foundation pillar, (4) overloaded by inhabitants with their usable items, and (5) filled up asides of the valley by filling materials which pressurized the pillar of the shed. Due to push or additional side pressure by filling materials to the foundation pillar, the pillar was moved and imbalanced the total shed and finally shed was suddenly subsided and collapsed by uniform settlement. Finally, it can be concluded that geological and engineering - geological study must be carried out for an urban hazard analyses in Rampura valley area as well as other valley areas in Dhaka city for future plan of urbanization and avoiding this type of urban hazard.